Analysis of Microplastic at Sea Water and Sediment in the Pasaran Island Bay Using FT-IR - Pamungkas, Galuh Rara; Widiastuti, Endang Linirin; Pratami, Gina Dania; Tugiyono, Tugiyono (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
Marine pollution from ocean garbage, particularly plastic waste, has significant ecological impacts globally. Plastic debris dominates marine pollution and graadually breaks down into microplastics. This study analyzes microplastic particle count, shapes, and polymer types in water and sediiment around Pasaran Island. Research was conducted across four stations (Station I, II, III, and IV). Microplastics in seawater samples were extracted using solutions of 70% ethanol, 30% H2O2, and 30% NaCl. Sediments were treated with FeSO4 (0.05 M), NaCl, and 30% H2O2. Particle counts and shapes were identified with a digital microscope and polymer types were determined via Fourier Transform Infrared Spectroscopy (FT-IR). Microplastic forms observed included fibers, fragments, film, and pellets, with fibers being the most abundant and pellets the least. Detected polymers included polyamide (PA), polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), and polytetrafluoroethylene (PTFE), originating from both local plasstic use and seawater flow around Pasaran Island.